ARCHEAN DIAMONDS FROM WAWA (CANADA): SAMPLES FROM DEEP CRATONIC ROOTS PREDATING CRATONIZATION OF THE SUPERIOR PROVINCE - Stachel T.; Banas A.; Muehlenbachs K.; Kurszlaukis S.; Walker E.C. (My University, 2006)
With an age of ca. 2.7 Ga, greenschist facies volcaniclastic rocks and lamprophyre dikes in the Wawa area (Superior Craton) host the only diamonds emplaced in the Archean available for study today. Nitrogen aggregation in Wawa diamonds ranges from Type IaA to IaB, suggesting mantle residence times of tens to hundreds of millions of years. The carbon isotopic composition (δ13C) of cube diamonds is similar to the accepted mantle value (-5.0‰). Octahedral diamonds show a slight shift (by + 1.5‰) to isotopically less negative values suggesting a subduction-derived, isotopically heavy component in the diamond-forming fluids. Syngenetic inclusions in Wawa diamonds are exclusively peridotitic and, similar to many diamond occurrences worldwide, are dominated by the harzburgitic paragenesis. Compositionally they provide a perfect match to inclusions from diamonds with isotopically dated Paleo- to Mesoarchean crystallization ages. Several high-Cr harzburgitic garnet inclusions contain a small majorite component suggesting crystallization at depth of up to 300 km. Combining diamond and inclusion data indicates that Wawa diamonds formed and resided in a very thick package of chemically depleted lithospheric mantle that predates stabilization of the Superior Craton. If late granite blooms are interpreted as final stages of cratonization then a similar disconnect between Paleo- to Mesoarchean diamondiferous mantle lithosphere and Neoarchean cratonization is also apparent in other areas (e.g., the Lac de Gras area of the Slave Craton) and may suggest that early continental nuclei formed and retained their own diamondiferous roots. © Springer-Verlag 2006.
Keywords: Докембрий::Архей::Неоархейская; Докембрий::Архей::Мезоархейская; Precambrian::Archean::Neoarchean; Precambrian::Archean::Mesoarchean